Oral feeding reduces hospitalizations compared with gastrostomy feeding in infants and children who aspirate - McSweeney, Maireade E. (J Pediatr, 2015)
OBJECTIVE: To compare the frequency of hospitalization rates between aspirating patients treated with gastrostomy versus those fed oral thickened liquids. STUDY DESIGN: A retrospective review was performed of patients with an abnormal videofluoroscopic swallow study between February 2006 and August 2013. 114 patients at Boston Children's Hospital were included. Frequency, length, and type of hospitalizations within one year of abnormal swallow study or gastrostomy tube placement were analyzed using a negative binomial regression model. RESULTS: Gastrostomy tube fed patients had a median of 2 (IQR: 1, 3) admissions per year as compared with orally fed patients who had a 1 (IQR: 0, 1) admissions per year, p<0.0001. Patients fed by gastrostomy were hospitalized for more days (median 24 (IQR: 6, 53) days) versus orally fed patients (median: 2 (IQR: 1, 4) days, (P<0.001)). Despite the potential risk of feeding patients orally, no differences in total pulmonary admissions (IRR: 1.65 (95%CI [0.70, 3.84])) between the two groups were found, except gastrostomy tube patients had 2.58 times (95%CI [1.02, 6.49]) more urgent pulmonary admissions. CONCLUSION: Patients who underwent gastrostomy tube placement for the treatment of aspiration had two times as many admissions as compared with aspirating patients fed orally. We recommend a trial of oral feeding in all children cleared to take nectar or honey thickened liquids prior to gastrostomy tube placement.